Penerapan Model Pembelajaran Make A Match Pada Materi Globalisasi Terhadap Hasil Belajar Siswa SD Negeri Blang Kiree - Nurmasyitah Nurmasyitah. (Jurnal Pesona Dasar, 2019)
This research entitled the application of models of learning make a match to content Globalization uterhadap student learning outcomes SD Blang Kiree. The problem in this research is how student learning outcomes by using cooperative learning models make a match to content globalization on class IV SD Blang Kiree. This research aims to know the results of the learning model cooperative learning using siswadengan make a match. This research uses qualitative research methods. The subject of research grade IV SD Blang Kiree totalling 25 persons. The conclusion that the application of the model make a match increases student learning results ketuntasan in SD Blang Kiree.